2022
DOI: 10.1111/twec.13374
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between trade openness and government size

Abstract: Does trade openness systematically imply bigger governments, as proposed by Rodrik (1998)? This paper presents a novel and more refined explanation for when and why international trade may enlarge the public sector. We propose that trade openness is associated with bigger governments if (i) the price volatility of a country's export basket is substantial and (ii) the country is democratic. The first condition satisfies the prior that open trade barriers indeed introduce uncertainty and external risk -something… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Based on panel data for 126 countries from 1980 to 2018, the relationship between trade openness and government size was negative in high-income countries but positive in low-income ones. Bharati et al [41] also found results endorsing the compensation hypothesis in their study of 137 countries. In a long-term analysis of Spain, Espuelas [42] found that trade openness positively affects social spending when fiscal capacity is high, but negatively when it is low, over the period 1850-2000.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 66%
See 1 more Smart Citation
“…Based on panel data for 126 countries from 1980 to 2018, the relationship between trade openness and government size was negative in high-income countries but positive in low-income ones. Bharati et al [41] also found results endorsing the compensation hypothesis in their study of 137 countries. In a long-term analysis of Spain, Espuelas [42] found that trade openness positively affects social spending when fiscal capacity is high, but negatively when it is low, over the period 1850-2000.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 66%
“…Their findings highlighted a causal relationship between openness and education expenditures, but only in low-income countries, providing no support for the compensation hypothesis. A variety of empirical studies have been conducted in recent years to elucidate the relationship between trade openness and government size [34][35][36][37][38][39][40][41][42][43]. For example, Lin et al [34] discovered that heightened trade openness enlarges the government size in small developing countries from 1985 to 2010.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%